Boiling Heat Transfer Simulation in Rectangular Mili-Channels - Koca, Aliihsan; Khalaji, Mansour Nasiri; Sepahyar, Soroush (Yıldız Teknik Üniversitesi, 2021)
Due to the high heat transfer coefficient and compactness of a system, mili-channel-based cooling and heating techniques are greatly expected to be distributing high heat flux from the electronic devices. In terms of cooling performance, the two-phase evaporating flow of boiling flow in mini and mili-channels is more effective than the single-phase flow due to the inclusion of latent energy in the process. In this study, a numerical model was proposed to simulate the boiling heat transfer of multiphase flow in a channel using different boundary conditions in the channel surfaces. The fluid volume approach regulating the hydrodynamics of the two-phase flow was used. Source terms of the energy and mass transfer that were taken into account at the interface of liquid and vapor were included in the management equations for the conservation of energy and vapor quality. A 3D Ansys-Fluent© simulation model was developed and numerical simulations were conducted for four different boundary conditions. A mili-channel with a length of 140 mm was used. The liquid and gas phases that were used in the model were liquid water and vapor; the total mass flux at the inlet was varied at 118–126 kg/m2s. In order to realize thin film annular flow over the boiler surface, employed specific boundary conditions in the 3D simulation model were obtained by means of one dimensional Matlab© simulation code. By means of utilizing the evaluated numerical results, distribution of heat transfer coefficient, vapor quality and dimensionless temperature over the heat transfer surfaces were reported and compared to experimental results. Numerically evaluated results are in agreement with experimentally measured results. For the studies cases an average value of 23600 W/m2.K was obtained for the heat transfer coefficient.
Keywords: Mili-Channel; Two-Phase Flow; Heat Transfer